DIKOTOMI ULAMA MENURUT AL-GHAZALY - Sa'dibih, Muhammad Ahmad Fulka Sa'dibih (Tamaddun, 2021)
The ideal scholars in the definition of Sayyid Qutub are people whothink and understand the book of Allah so that they can know Allahthrough His creation, find Allah with all His power, feel the majesty ofAllah by seeing the nature of His creation, so that they become trulyafraid, pious. and actually worship it. However, al-Ghazaly in the bookIhya'Ulumuddin states the dichotomy of scholars, namely there arescholars of the world and there are scholars of the hereafter. This articlewill describe the dichotomy of scholars and the criteria for each.